Using sequence analysis to test if human life histories are coherent strategies - Sheppard, P; Van Winkle, Z (Cambridge University Press, 2020)
Life history theory, a prominent ecological model in biology, is widely used in the human sciences to make predictions about human behaviour. However, its principle assumptions have not been empirically tested. We address this gap with three research questions: 1) do humans exhibit coherent life history strategies, 2) do individuals adopt strategies along a slow-fast continuum, and 3) are socioeconomic circumstances during childhood associated with the pace of the life history strategy that an individual adopts? Data from the Wisconsin Longitudinal Study is used to reconstruct the life histories of US Women including information on puberty, fertility, menopause, and death. We introduce a novel methodological approach to evolutionary anthropology, sequence analysis, to assess if human life histories are coherent strategies and how these strategies are patterned. In subsequent analyses we used multinomial logistic regressions to test whether childhood socioeconomic status predicts the life history patterns women follow. Results provide little evidence that humans follow coherent life-history strategies; Wisconsin women are clustered by the number of children they have but not by ages at life events. Socioeconomic status does not predict which cluster women fall into, suggesting that less well-off women do not have higher fertility, as predicted.